Properties Of Coconut Fibre Based Particleboard Bonded With Modified Potato Starch - Adedoja, Owodunni Amina (2020)
Adhesives based on potato starch have been studied as an alternative binder for particleboards due to their rheological, environmentally friendly, and inexpensive properties. In this research, particleboards were manufactured from coconut fibre and bonded with green adhesives produced from potato starch, the adhesive was modified with citric acid as well as glutardialdehyde